2001
DOI: 10.1094/pdis.2001.85.7.801a
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Chilli veinal mottle virus in Solanum aethiopicum in Tanzania

Abstract: African eggplant, or garden egg (Solanum aethiopicum) is an important vegetable in most sub-Saharan African countries. Since June 1997, viral symptoms, including mosaic, vein clearing, and stunting, have been observed on several crops of African eggplant cv. Tengeru White at a number of sites in the Arusha region of northern Tanzania. Field inspections revealed disease incidence ranging from 50 to 90%. During the same period, high populations of the green peach aphid Myzus persicae were observed in affected cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…The related region is exposed on the surface of the virus particle and is the major virus‐specific epitope of potyviruses (Shukla & Ward, 1989; Urcuqui‐Inchima et al ., 2001). Because of the serological cross reaction, the recently detected ChiVMV in Tanzania by DAS‐ELISA (Nono‐Womdim et al ., 2001) should be confirmed by the virus sequence identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The related region is exposed on the surface of the virus particle and is the major virus‐specific epitope of potyviruses (Shukla & Ward, 1989; Urcuqui‐Inchima et al ., 2001). Because of the serological cross reaction, the recently detected ChiVMV in Tanzania by DAS‐ELISA (Nono‐Womdim et al ., 2001) should be confirmed by the virus sequence identification.…”
Section: Discussionmentioning
confidence: 99%
“…The virus is widely distributed in Asia, including China, India, Indonesia, Korea, Malaysia, the Philippines, Taiwan, and Thailand (Green & Kim, 1991; Siriwong et al ., 1995; Ravi et al ., 1997; Wang et al ., 2006). Recently, ChiVMV was also detected outside Asia, in Tanzania, by double antibody sandwich enzyme‐linked immunosorbent assay (DAS‐ELISA) (Nono‐Womdim et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Rendahnya produktivitas cabai nasional disebabkan oleh berbagai serangan hama dan penyakit, salah satunya adalah infeksi virus chilli veinal mottle virus (ChiVMV) yang dikenal sebagai virus belang (Womdim et al, 2001). Penyakit ini menyerang tanaman cabai sejak awal pertumbuhan hingga stadia panen sehingga sangat berpengaruh terhadap produktivitas cabai.…”
Section: Pendahuluanunclassified
“…The conserved amino acids FDSS at position 2,546-2,549 of the polyprotein was located 263 aa upstream of the putative NIb/CP cleavage site [33]. The conserved (S/ T)G-(X) 3 -T(X) 3 -N(S/T)(X) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] GDD that is necessary for RNA polymerase activity and NTP binding began at position 2,604. In CP, the DAG motif that interacts with PTK of HC-Pro to regulate potyviruses transmission by aphids [34] was located at position 2,815-2,817.…”
Section: Conservative Motifs Of Tvbmv-ynd and Other Potyvirusesmentioning
confidence: 99%
“…Phylogenetic analysis revealed that TVBMV-YND was most closely related to ChiVMV, a virus reported in Asia and Africa and which mainly infects solanaceous plants [35,36] (Fig. 2).…”
Section: Phylogenetic Analysis Of Tvbmv-yndmentioning
confidence: 99%